2022
DOI: 10.1002/cjoc.202200483
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Conformational Transition of Polypeptides under Slightly Acidic Environment

Abstract: Comprehensive Summary Controlling the conformational transition of polypeptides under slightly acidic environment is challenging. Herein, we report a class of pH‐responsive helix‐to‐coil conformationally transitionable polypeptides (pCTPs) by simply conjugating tertiary amine groups (TAs) to polylysine. Their conformation is highly dependent on the charge state of TAs, showing a helical structure when most TAs are deprotonated and a non‐helical structure when majority of TAs are protonated. The conformational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This property allows polypeptides to specifically target cells in tissues with lower extracellular pH. 84,85 The glycopeptides designed by Schlaad et al formed an α-helix under acidic conditions (pH 3.5). 86 The α-helix was stable and resistant to degradation, and once formed, it had good water solubility, making it suitable for drug delivery systems.…”
Section: Research Progress In Self-assmbly Of Ph-responsive Polypeptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…This property allows polypeptides to specifically target cells in tissues with lower extracellular pH. 84,85 The glycopeptides designed by Schlaad et al formed an α-helix under acidic conditions (pH 3.5). 86 The α-helix was stable and resistant to degradation, and once formed, it had good water solubility, making it suitable for drug delivery systems.…”
Section: Research Progress In Self-assmbly Of Ph-responsive Polypeptidesmentioning
confidence: 99%
“…Xiong et al reported a class of pH-responsive polypeptides (pCTP) capable of transitioning from a α-helical to a coiled conformation. 84 When the conformation of pCTP changes from α-helix to coil, it exhibits a transformation from vesicles to micelles, serving as an intelligent carrier for controlled drug release. This study provided a method to control the conformational transition of polypeptides under mildly acidic conditions, which can be used as a tool for targeted delivery of drugs or imaging probes to tissues with low extracellular pH.…”
Section: Research Progress In Self-assmbly Of Ph-responsive Polypeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…31−37 Additionally, amphiphilic polypeptides with αhelical hydrophobic segments tend to self-assemble into vesicles due to the parallel arrangement of rigid helices, while their β-sheet and random-coiled analogues are more likely to form micelles. 20,22,38 Due to the distinct differences of materials properties between helical and random-coiled conformation, conformation-switchable polypeptides are designed and synthesized to manipulate their biomedical functions in situ. The transition of secondary structures is achieved through the fine-tuning of side-chain interactions including electrostatic interactions, 39−42 polarity, 43−47 hydrogen bonds, 48 coordination interaction, 49 and base-pairing interactions, 50 which activates or deactivates the helixassociated functions under desired conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Synthetic polypeptides have displayed great potentials in the biomedical field and are regarded as promising candidates for the design of drug carriers due to their desired biocompatibility and biodegradability. As protein mimics, polypeptides can adopt ordered secondary structures (e.g., α-helix and β-sheet) through hydrogen bonding interactions between backbone peptide bonds, which endow them with conformation-specific assembly behaviors and biomedical functions. For instance, cationic polypeptides with α-helical structures exhibit much higher membrane-penetrating activity than their random-coiled analogues, which are internalized through the “pore-formation” mechanism. Through proper side-chain design, α-helical, cationic polypeptides have been widely studied to promote the intracellular delivery of molecular cargos or to facilitate the design of antimicrobial or antitumor polymers. Additionally, amphiphilic polypeptides with α-helical hydrophobic segments tend to self-assemble into vesicles due to the parallel arrangement of rigid helices, while their β-sheet and random-coiled analogues are more likely to form micelles. ,, Due to the distinct differences of materials properties between helical and random-coiled conformation, conformation-switchable polypeptides are designed and synthesized to manipulate their biomedical functions in situ . The transition of secondary structures is achieved through the fine-tuning of side-chain interactions including electrostatic interactions, polarity, hydrogen bonds, coordination interaction, and base-pairing interactions, which activates or deactivates the helix-associated functions under desired conditions.…”
Section: Introductionmentioning
confidence: 99%